Efficacy of antitachycardia pacing for electrical storms in patients with implantable defibrillators. (2nd February 2021) - Hayashi, Hiroshi; Shimizu, Wataru; Iwasaki, Yuki; Yodogawa, Kenji; Noda, Takashi; Nitta, Takashi; Aizawa, Yoshifusa; Ohe, Tohru; Kurita, Takashi
Abstract: Introduction: Although antitachycardia pacing (ATP) is effective in terminating ventricular tachyarrhythmias in patients with implantable cardioverter defibrillators (ICDs), the efficacy of ATP during an electrical storm (ES) and the positive impact on all‐cause mortality have not been fully elucidated. Methods and Results: From 2010 to 2012, 1570 patients who underwent ICD implantation in 48 ICD centers in Japan were enrolled in the study and prospectively followed up. Patients with long QT syndrome, Brugada syndrome, and idiopathic ventricular fibrillation were excluded. The prevalence of shocks during ESs and impact on the all‐cause mortality were evaluated. During a median follow‐up of 28 months, there were 127 ESs in 84 patients. Of those 127 ESs, 80 ESs (63%) in 37 patients were treated by only ATP and the remaining 47 ESs in 47 patients required at least one shock. The lower ventricular rate of the initial arrhythmia during ES (odds ratio [OR]: 1.02 per unit; 95% confidence interval [CI]: 1.00–1.04; p = .02) and narrower QRS complex (OR: 1.03 per unit; 95% CI: 1.01–1.06; p < .01) were the independent predictors of ATP success during the ES. The patients treated with ATP alone tended to have lower all‐cause mortality compared to those that required shocks during the ES (log‐rank p = .10). Conclusions: ATP was effective in patients suffering from ESs as it avoided painful shocks in more than half of the cases. Patients who received only ATP during ES tended to have lower mortality compared to those who received the shock.